HUBUNGAN PENDAMPINGAN KELUARGA TERHADAP KEPATUHAN MINUM OBAT ANTI HIPERTENSI PADA PENDERITA HIPERTENSI DI DESAWATUKOSEK KECAMATAN GEMPOLKABUPATEN PASURUAN - Zainuri, Imam; Oktovany, Rizka (JURNAL KEPERAWATAN SEHAT, 2015)
Hypertension is the most common disease by the Indonesian population due to hypertensive disease appears without complaint. Pharmacologic management of hypertension is by taking anti-hypertensive medication. The facts show that, still often found in hypertensive patients who are not regularly in anti-hypertensive drugs. The purpose of this study was to determine the relationship of family assistance to anti-hypertensive medication adherence in hypertensive patients in the village Watukosek Gempol District of Pasuruan. Design research is a correlation - a retrospective observation. The number of samples in this study is 71 respondents drawn from 86 patients with simple random sampling technique. The variables in this study the family assistance in taking antihypertensive drugs and antihypertensive medication adherence in patients with hypertension. The research instrument used was a questionnaire. To determine the relationship of family assistance to anti-hypertensive medication adherence in hypertensive patients in the village Watukosek Gempol District of Pasuruan used chi square correlation test. If the significance value obtained is less than α (0.05), the research hypothesis H0 is rejected and H1 accepted meaning, there is a relationship between family assistance to anti-hypertensive medication adherence in hypertensive patients in the village Watukosek Gempol District of Pasuruan. The results showed an association between family assistance to anti-hypertensive medication adherence in hypertensive patients in the village Watukosek Gempol District of Pasuruan with a significance value of 0.000. The higher forms of support given to the family of the compliance of patients with hypertension in patients with hypertension taking anti-hypertensive drugs will better.Keywords: adherence, family assistance, hypertension